Analisis Strategi Bauran Pemasaran Terhadap Minat Pembelian Air Minum dalam Kemasan Bariklana Desa Parseh Kecamatan Socah Bangkalan - Bastoni; Tarman, Manah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to analyze the effect of marketing mix on buying interest. This research uses a quantitative approach. This research was conducted on 50 consumers and the data collection methods used included questionnaires, interviews and observations. The results of this study prove that the independent variables X1 (people), X2 (promotion), X3 (people), and X4 (process) and X5 (physical evidence) have a positive influence on the dependent variable Y (purchase interest) because the sig value below 0.05 indicates a statistically significant value.